An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte

By using elastic electrolyte in an all-solid state battery closely combined with the alloy-type negative electrode, the interfacial instability problem caused by volume changes during the charge and discharge process of the alloy-type negative electrode is solved, and an all-solid state battery with high cycling performance and long life is achieved.

CN115425287BActive Publication Date: 2025-03-18BEIJING UNIV OF CHEM TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211207102.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-03-18
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The huge volume expansion and contraction of alloy negative electrodes during charging and discharging leads to material crushing, increased side reactions and unstable interface of solid electrolytes, which in turn hinders its cyclic performance and practical application.

Method used

The elastic electrolyte with super-large deformation capability is closely combined with the alloy-type negative electrode. Through the compression and expansion adjustment of the elastic electrolyte, the impact of the negative electrode volume changes on the internal pressure on the battery is dynamically adaptively, and the interface contact stability between the negative electrode and the lithium conduction layer is improved.

Benefits of technology

Effectively slows down the capacity attenuation of alloy negative electrode solid-state batteries, improves circulation performance, extends battery life, and improves battery safety and mechanical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115425287B_ABST
    Figure CN115425287B_ABST
Patent Text Reader

Abstract

The present invention relates to an all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte. The battery is composed of an alloy-type negative electrode, an elastic electrolyte and a positive electrode; the elastic electrolyte comprises an elastic polymer matrix and a metal salt, and optionally comprises a plasticizer; wherein the content of the elastic polymer is 20 to 95 wt.%, the content of the metal salt is 5 to 50 wt.%, and the content of the plasticizer is 0 to 50 wt.%; the ionic conductivity of the elastic electrolyte is (0.5 to 100.0)×10 ‑4 S cm ‑1 , thickness is 5 to 1000 μm, elastic deformation is 50 to 500%. The elastic electrolyte can dynamically adapt to the volume shrinkage / expansion of the alloy-type negative electrode during charging and discharging, ensure good interface contact between the electrolyte and the negative electrode, solve the problem of continuous capacity attenuation of alloy-type negative electrode solid-state batteries caused by insufficient and unstable interface contact, and improve the cycle performance of alloy-type negative electrode solid-state batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of solid-state batteries and relates to an all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte. Background Art

[0002] Alloy anode has a higher theoretical specific capacity than traditional intercalation anode and can be used to construct high specific energy primary and secondary batteries. Taking silicon anode as an example, its theoretical specific capacity as anode material for lithium-ion batteries is 3759 mAh g -1 (Li 15 Si4), a commercial graphite anode (372mAh g -1 The theoretical energy density of lithium-ion batteries using silicon as the negative electrode material can reach 400Wh kg -1 , which has good application prospects in the fields of electric vehicles and large-scale energy storage. However, the alloy negative electrode will undergo a huge volume expansion during the charging and discharging process (for example, the volume expansion of the silicon negative electrode can reach more than 300% during the lithium storage process). The huge volume effect causes the material to pulverize, resulting in continuous side reactions between the alloy negative electrode and the organic electrolyte, producing an unstable solid electrolyte interface (SEI), causing the alloy negative electrode to irreversibly lose electrical contact, and the rapidly deteriorating cycle performance hinders the practical application of the alloy negative electrode.

[0003] At present, the methods for improving the cycle stability of alloy-type negative electrodes include nano-sizing, carbon composite, adhesive modification and electrolyte modification. Among them, electrolyte modification can fundamentally improve the structural stability of SEI and is considered to be the most effective modification method for alloy-type negative electrodes. Unlike electrolytes, the use of solid electrolytes can significantly reduce the lithium-silicon alloy / electrolyte interface, effectively inhibit the formation of SEI, and at the same time slow down the continuous growth of new SEI caused by volume expansion of the negative electrode, thereby improving the cycle stability of the alloy-type negative electrode. However, both inorganic solid electrolytes and conventional polymer electrolytes have the problem of insufficient solid-solid interface contact with the alloy-type negative electrode, and cannot effectively alleviate the huge volume effect of the alloy zinc negative electrode during the charge and discharge cycle, reducing the cycle life, energy density and power density of the solid-state full battery. The above problems also hinder the commercial application of high-performance solid-state batteries based on alloy-type negative electrodes. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides an all-solid-state battery containing an elastic electrolyte and an alloy-type negative electrode. The elastic electrolyte is tightly pressed with the alloy-type negative electrode and the positive electrode to obtain an all-solid-state battery. The elastic electrolyte has a very large deformation amount, and its elastic modulus is significantly higher than that of common solid polymer electrolytes, inorganic solid electrolytes and liquid electrolytes. The alloy-type negative electrode expands during the lithium insertion process, and the elastic electrolyte tightly combined with the alloy-type negative electrode is compressed under pressure, which can slow down the influence of the expansion of the alloy-type negative electrode on the internal pressure of the solid-state battery. The alloy-type negative electrode shrinks in volume during the lithium removal process, and the elastic electrolyte tightly combined with the alloy-type negative electrode expands under reduced pressure, which can alleviate the interface contact problem caused by the shrinkage of the alloy-type negative electrode. In summary, the elastic electrolyte can make dynamic adaptive adjustments to the volume shrinkage / expansion caused by the lithium removal process of the alloy-type negative electrode, solve the problem of unstable interface contact between the alloy-type negative electrode / lithium conductive layer during the operation of the solid-state battery, thereby slowing down the capacity decay of the alloy-type negative electrode solid-state battery, improving the cycle performance of the alloy-type negative electrode solid-state battery, and then assembling with the positive electrode material to obtain a high-capacity, long-life, and cycle-stable all-solid-state battery.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions:

[0006] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte comprises an alloy-type negative electrode, an elastic electrolyte and a positive electrode.

[0007] In a preferred embodiment of the present invention, the alloy-type negative electrode is fixed to the side of the current collector, and the elastic electrolyte is located between the negative electrode and the positive electrode.

[0008] In a preferred embodiment of the present invention, the all-solid-state battery is selected from a primary or secondary battery; further, the all-solid-state battery is selected from any one of a lithium battery, a sodium battery, a potassium battery, a magnesium battery, a calcium battery, and an aluminum battery.

[0009] In a preferred embodiment of the present invention, the alloy-type negative electrode includes a metal / non-metal and a compound thereof that can form an alloy with a metal ion; further, the metal ion is any one of lithium ions, sodium ions, potassium ions, magnesium ions, calcium ions, and aluminum ions.

[0010] In a preferred embodiment of the present invention, the elastic electrolyte is tightly combined with the alloy-type negative electrode and the positive electrode in an in-situ or ex-situ manner; further, the combination method includes any one of the following methods:

[0011] (1) After the elastic electrolyte is pre-cured, it is coated on one side of the alloy-type negative electrode and continues to cure;

[0012] (2) After the elastic electrolyte is pre-cured, it is coated on one side of the alloy type negative electrode, and after being attached to the positive electrode, it continues to cure;

[0013] (3) The precursor solution of the elastic electrolyte is injected between the alloy-type negative electrode and the positive electrode and solidified.

[0014] In a preferred embodiment of the present invention, the elastic electrolyte comprises an elastic polymer matrix and a metal salt; optionally, the elastic electrolyte further comprises a plasticizer; wherein the content of the elastic polymer is 30 to 85 wt.%, the content of the lithium salt is 5 to 50 wt.%, and the content of the plasticizer is 0 to 50 wt.%.

[0015] In a preferred embodiment of the present invention, the elastic polymer matrix includes one or more of a thermosetting elastomer, a thermoplastic elastomer, or a copolymer or mixture with the above-mentioned thermosetting / thermoplastic elastomer as the main body; further, the thermosetting elastomer is selected from one or more of natural rubber, isoprene rubber, polybutadiene rubber, styrene-butadiene rubber, nitrile rubber, and chloroprene rubber; the thermoplastic elastomer is selected from one or more of hydrogenated ethylene-butylene rubber, polyamide, vinyl acetate, polyolefin, and polyurethane.

[0016] In a preferred embodiment of the present invention, the metal salt includes one or more of an inorganic salt and an organic salt; further, the inorganic salt is selected from one or more of perchlorate, tetrafluoroborate, hexafluoroarsenate, and hexafluorophosphate, and the organic salt is selected from one or more of bis(oxalate)borate, difluorooxalate borate, bis(difluorosulfonyl)imide salt, and bis(trifluoromethyl)sulfonyl imide salt. The metal ions of the metal salt in the electrolyte can be conducted through the electrolyte and serve as carriers of the solid-state battery.

[0017] In a preferred embodiment of the present invention, the plasticizer in the electrolyte includes one or more organic molecules and ionic liquids such as alcohols, phenols, ethers, acids, aldehydes, ketones, esters, nitriles, amines, etc. In addition, the plasticizer can not only promote the elastic electrolyte molecular chain to transport metal ion carriers, but also part of the plasticizer can cross-link with the elastic electrolyte molecular chain to improve the mechanical properties of the elastic electrolyte.

[0018] In a preferred embodiment of the present invention, the ionic conductivity of the elastic electrolyte is 0.5×10 -4 ~100.0×10 -4 S cm -1 , thickness is 5 to 1000 μm, elastic deformation is 50 to 500%, and has flame retardant properties.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. In terms of battery assembly process, the three assembly methods adopted by the present invention are simple in process and have good modification effect. After the elastic electrolyte is pre-cured, it continues to cure on the surface of the alloy-type negative electrode, which can improve the tightness of the elastic electrolyte and the alloy-type negative electrode, and promote the elastic electrolyte to be super-conformal with the alloy-type negative electrode during the lithium deintercalation process, reduce the interface impedance between the elastic electrolyte and the alloy-type negative electrode, and improve the cycle life of the solid-state alloy-type negative electrode battery. After the positive electrode is attached to the pre-cured elastic electrolyte, it continues to cure, which can improve the tightness of the positive electrode and the elastic electrolyte, reduce the interface impedance between the positive electrode and the elastic electrolyte, and improve the capacity of the alloy-type negative electrode solid-state battery. The elastic electrolyte is in-situ cured between the alloy-type negative electrode and the positive electrode and in the pores of the two electrodes. The elastic electrolyte is bound to the surface of the alloy-type negative electrode particles during the lithium deintercalation process of the alloy-type negative electrode, promotes the transport of lithium ions between the alloy-type negative electrode and the positive electrode, and improves the cycle performance of the alloy-type negative electrode solid-state battery.

[0021] 2. In terms of battery performance, the elastic electrolyte used in the solid-state battery designed by the present invention has a large deformation amount, and its elastic modulus is significantly higher than that of common solid polymer electrolytes, inorganic solid electrolytes and liquid electrolytes. The elastic electrolyte has a large deformation amount, and can dynamically adapt to the significant volume contraction / expansion of the alloy-type negative electrode during the charge and discharge process, ensuring the close contact between the elastic electrolyte and the alloy-type negative electrode, thereby slowing down the capacity decay of the alloy-type negative electrode solid-state battery and improving the cycle performance of the solid-state alloy-type negative electrode battery.

[0022] 3. In terms of battery safety, the present invention designs an all-solid-state battery containing an elastic electrolyte and an alloy-type negative electrode. The elastic electrolyte is tightly pressed with the alloy-type negative electrode and positive electrode to obtain an all-solid-state battery. The all-solid-state battery involved in the present invention has flame retardancy and excellent mechanical properties. The alloy-type negative electrode used has a higher capacity than the traditional intercalation-type negative electrode and has higher safety than the metal lithium negative electrode. Therefore, the all-solid-state battery designed by the present invention has better safety than traditional solid-state electrolyte batteries or liquid electrolyte batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0024] Figure 1 Schematic diagram of battery structure;

[0025] Figure 2 A stress-strain curve of the elastic electrolyte prepared in Example 1 of the present invention;

[0026] Figure 3 Flame retardant properties of the elastic electrolyte prepared in Example 1 of the present invention;

[0027] Figure 4 Ionic conductivity of the elastic electrolyte prepared in Example 1 of the present invention;

[0028] Figure 5 The performance of the elastic electrolyte lithium symmetric battery prepared in Example 1 of the present invention;

[0029] Figure 6 Performance of a full battery assembled with the elastic electrolyte prepared in Example 1 of the present invention, a silicon negative electrode and a lithium iron phosphate positive electrode. DETAILED DESCRIPTION

[0030] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0031] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0032] Example 1

[0033] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0034] 0.375 g of nitrile rubber is weighed, dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle, stirred at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, and then the sample bottle is transferred to a glove box in an argon atmosphere; 0.1875 g of lithium bis(trifluoromethylsulfonyl)imide is added to the glove box, the solution is sealed and taken out, and the solution is continuously stirred on a hot stage at 60° C. for 12 hours; after cooling to room temperature, the colloid in the sample bottle is taken out and placed on a clean glass plate, and a 750 μm scraper is used to scrape to obtain a flat and uniform electrolyte liquid film, which is evaporated and dried at room temperature for 8 hours and then transferred to a vacuum drying oven, and cured at 60° C. and -0.1 MPa for 12 hours to obtain the elastic electrolyte.

[0035] The silicon negative electrode, the elastic electrolyte, and the lithium iron phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state lithium battery containing the alloy-type negative electrode and the elastic electrolyte.

[0036] Example 2 (nitrile rubber replaced by polyurethane)

[0037] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0038] 0.375 g of polyurethane was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box with an argon atmosphere. 0.1875 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, which was sealed and taken out, and continued to be stirred on a hot stage at 60° C. for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a clean glass plate, and a 750 μm scraper was used to scrape to obtain a flat and uniform electrolyte liquid film, which was evaporated and dried at room temperature for 8 hours and then transferred to a vacuum drying oven, and cured at 60° C. and -0.1 MPa for 12 hours to obtain the elastic electrolyte.

[0039] The silicon negative electrode, the elastic electrolyte, and the lithium iron phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state battery containing the alloy-type negative electrode and the elastic electrolyte.

[0040] Example 3 (Lithium bis(trifluoromethylsulfonyl)imide replaced with lithium perchlorate)

[0041] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0042] 0.375 g of nitrile rubber is weighed, dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle, stirred at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, and then the sample bottle is transferred to a glove box with an argon atmosphere; 0.1875 g of lithium perchlorate is added to the glove box, which is sealed and taken out, and is continuously placed on a hot stage at 60° C. and stirred for 12 hours; after cooling to room temperature, the colloid in the sample bottle is taken out and placed on a clean glass plate, and a 750 μm scraper is used to scrape to obtain a flat and uniform electrolyte liquid film, which is evaporated and dried at room temperature for 8 hours, then transferred to a vacuum drying oven, and cured at 60° C. and -0.1 MPa for 12 hours to obtain the elastic electrolyte.

[0043] The silicon negative electrode, the elastic electrolyte, and the lithium iron phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state battery containing the alloy-type negative electrode and the elastic electrolyte.

[0044] Example 4 (Variation of polymer content)

[0045] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0046] 0.75 g of nitrile rubber is weighed, dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle, stirred at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, and then the sample bottle is transferred to a glove box with an argon atmosphere; 0.1875 g of lithium perchlorate is added to the glove box, which is sealed and taken out, and is continuously stirred on a hot stage at 60° C. for 12 hours; after cooling to room temperature, the colloid in the sample bottle is taken out and placed on a clean glass plate, and a 750 μm scraper is used to scrape to obtain a flat and uniform electrolyte liquid film, which is evaporated and dried at room temperature for 8 hours, then transferred to a vacuum drying oven, and cured at 60° C. and -0.1 MPa for 12 hours to obtain the elastic electrolyte.

[0047] The silicon negative electrode, the elastic electrolyte, and the lithium iron phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state battery containing the alloy-type negative electrode and the elastic electrolyte.

[0048] Example 5 (Salt content changed to 50%)

[0049] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0050] 0.375 g of nitrile rubber was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box with an argon atmosphere, 0.375 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, the sample was taken out after sealing, and the sample was placed on a hot stage at 60° C. and stirred for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a clean glass plate. A 750 μm scraper was used to scrape to obtain a smooth and uniform electrolyte liquid film. After volatilization and drying at room temperature for 8 hours, the sample was transferred to a vacuum drying oven and cured at 60° C. and −0.1 MPa for 12 hours to obtain the elastic electrolyte.

[0051] The silicon negative electrode, the elastic electrolyte, and the lithium iron phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state battery containing the alloy-type negative electrode and the elastic electrolyte.

[0052] Example 6 (fluoroethylene carbonate is a plasticizer, content 10wt.%)

[0053] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0054] 0.375 g of nitrile rubber was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealed 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box in an argon atmosphere, 0.1875 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, the sample was taken out after sealing, and the sample was placed on a hot stage at 60° C. and stirred for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a clean glass plate. A 750 μm scraper was used to scrape and apply to obtain a flat and uniform electrolyte liquid film. After volatilization and drying at room temperature for 8 hours, the sample was transferred to a vacuum drying oven, cured at 60° C. and -0.1 MPa for 12 hours, and then transferred to a glove box, and swelled with 10 wt.% fluoroethylene carbonate to obtain the elastic electrolyte.

[0055] The silicon negative electrode, the elastic electrolyte, and the lithium iron phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state battery containing the alloy-type negative electrode and the elastic electrolyte.

[0056] Example 7 (fluoroethylene carbonate is a plasticizer, content 20wt.%)

[0057] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0058] 0.375 g of nitrile rubber was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box in an argon atmosphere, 0.1875 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, the sample was taken out after sealing, and the sample was placed on a hot stage at 60° C. and stirred for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a clean glass plate. A 750 μm scraper was used to scrape and apply to obtain a smooth and uniform electrolyte liquid film. After volatilization and drying at room temperature for 8 hours, the film was transferred to a vacuum drying oven, cured at 60° C. and −0.1 MPa for 12 hours, and then transferred to a glove box to swell 20 wt.% of fluoroethylene carbonate to obtain the elastic electrolyte.

[0059] The silicon negative electrode, the elastic electrolyte, and the lithium iron phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state battery containing the alloy-type negative electrode and the elastic electrolyte.

[0060] Example 8 (technical solution changed to in-situ bonding positive electrode)

[0061] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0062] 0.375 g of nitrile rubber was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box with an argon atmosphere, 0.1875 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, the sample was taken out after sealing, and the sample was placed on a hot stage at 60° C. and stirred for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a dry lithium iron phosphate positive electrode sheet. A 750 μm scraper was used to scrape the positive electrode to obtain a flat and uniform electrolyte liquid film on the surface of the positive electrode. After volatilization and drying at room temperature for 8 hours, the sample was transferred to a vacuum drying oven and cured at 60° C. and -0.1 MPa for 12 hours to obtain the in-situ combined elastic electrolyte-positive electrode.

[0063] The in-situ combined electrolyte is packaged with a lithium iron phosphate positive electrode and a silicon negative electrode to obtain the all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte.

[0064] Example 9 (technical solution replaced with in-situ bonding of negative electrode)

[0065] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0066] 0.375 g of nitrile rubber was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box with an argon atmosphere, 0.1875 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, the sample was taken out after sealing, and the sample was placed on a hot stage at 60° C. and stirred for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a dry silicon negative electrode sheet. A 750 μm scraper was used to scrape the negative electrode to obtain a smooth and uniform electrolyte liquid film on the surface of the negative electrode. After volatilization and drying at room temperature for 8 hours, the sample was transferred to a vacuum drying oven and cured at 60° C. and -0.1 MPa for 12 hours to obtain the in-situ combined elastic electrolyte-positive electrode.

[0067] The in-situ combined electrolyte is packaged with a silicon negative electrode and a lithium iron phosphate positive electrode to obtain the all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte.

[0068] Example 10 (phosphorus anode replaces silicon anode, and lithium bis(trifluoromethylsulfonylimide) is replaced by sodium bis(trifluoromethylsulfonylimide)

[0069] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0070] 0.375 g of nitrile rubber was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box with an argon atmosphere, 0.1875 g of sodium bis(trifluoromethylsulfonyl)imide was added to the glove box, the solution was sealed and taken out, and continued to be stirred on a hot stage at 60° C. for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a clean glass plate. A 750 μm scraper was used to scrape to obtain a smooth and uniform electrolyte liquid film. After volatilization and drying at room temperature for 8 hours, the solution was transferred to a vacuum drying oven and cured at 60° C. and −0.1 MPa for 12 hours to obtain the elastic electrolyte.

[0071] The phosphorus negative electrode, elastic electrolyte, and sodium vanadium phosphate positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state lithium battery containing the alloy negative electrode and the elastic electrolyte.

[0072] Example 11 (NCM523 positive electrode instead of lithium iron phosphate positive electrode)

[0073] An all-solid-state battery containing an alloy-type negative electrode and an elastic electrolyte, wherein the technical solution is as follows:

[0074] 0.375 g of nitrile rubber was weighed and dissolved in a mixed solution of 1.25 ml of acetone and 2.5 ml of xylene in a completely sealable 20 ml sample bottle. After stirring at a speed of 500 r / min on a hot stage at 60° C. for 6 hours, the sample bottle was transferred to a glove box with an argon atmosphere, 0.1875 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, the sample was taken out after sealing, and the sample was placed on a hot stage at 60° C. and stirred for 12 hours. After cooling to room temperature, the colloid in the sample bottle was taken out and placed on a clean glass plate. A 750 μm scraper was used to scrape to obtain a smooth and uniform electrolyte liquid film. After volatilization and drying at room temperature for 8 hours, the sample was transferred to a vacuum drying oven and cured at 60° C. and −0.1 MPa for 12 hours to obtain the elastic electrolyte.

[0075] The silicon negative electrode, the elastic electrolyte, and the NCM523 positive electrode are sequentially assembled and packaged in a 2032-type button battery to obtain the all-solid-state lithium battery containing the alloy-type negative electrode and the elastic electrolyte.

[0076] Comparative Example 1:

[0077] An all-solid-state battery based on non-elastic PEO, the technical solution is:

[0078] Weigh 0.44g PEO and dissolve it in 10ml acetonitrile solution in a completely sealable 20ml sample bottle. Stir at room temperature at a speed of 500r / min for 6h, then transfer the sample bottle to a glove box with argon atmosphere, add 0.22g lithium bis(trifluoromethylsulfonyl)imide into the glove box, seal it and take it out, continue to stir at room temperature on a stirring table for 12h, take out the colloid in the sample bottle with a rubber-tipped dropper and place it in a polytetrafluoroethylene mold with a diameter of 14cm. After volatilization and drying at room temperature for 8h, transfer it to a vacuum drying oven and dry it at 60℃ and -0.1MPa for 12h to obtain a PEO solid electrolyte.

[0079] The all-solid-state lithium battery can be obtained by sequentially combining and packaging the silicon negative electrode, the PEO-based electrolyte, and the lithium iron phosphate positive electrode in a 2032-type button battery.

[0080] Comparative Example 2:

[0081] An all-solid-state battery based on non-elastic PEO, the technical solution is:

[0082] 0.44 g of PEO was weighed and dissolved in 10 ml of acetonitrile solution in a completely sealable 20 ml sample bottle. After stirring at 500 r / min for 6 hours at room temperature, the sample bottle was transferred to a glove box with an argon atmosphere, 0.22 g of lithium bis(trifluoromethylsulfonyl)imide was added to the glove box, and the mixture was sealed and taken out. Stirring was continued on a stirring table at room temperature for 12 hours. The colloid in the sample bottle was taken out with a rubber-tipped dropper and placed in a polytetrafluoroethylene mold with a diameter of 14 cm. After volatilization and drying at room temperature for 8 hours, the mixture was dried at 60° C. and −0.1 MPa for 12 hours, transferred to a glove box, and swollen with 10 wt.% fluoroethylene carbonate to obtain the elastic electrolyte.

[0083] The all-solid-state lithium battery can be obtained by sequentially combining and packaging the silicon negative electrode, the PEO-based electrolyte, and the lithium iron phosphate positive electrode in a 2032-type button battery.

[0084] Experimental Example 1:

[0085] Basic tests were performed on the elastic electrolytes prepared in Examples 1 to 7, and the experimental results are shown in Table 1:

[0086] Table 1 Basic test data of elastic electrolytes prepared in Examples 1 to 7 and Comparative Examples 1-2

[0087]

[0088]

[0089] Experimental Example 2:

[0090] The elastic electrolyte prepared in Examples 1 to 7 was cut into discs with a diameter of 16 cm and assembled with metal lithium / metal sodium to form a Li||Li(Na||Na) symmetrical battery, where the metal electrode diameter was 14 cm and the button-type symmetrical battery model was CR2032. -2 Current density, 0.1 mAh cm -2 The test conditions for the symmetrical battery long cycle test were 60°C. The test results are shown in Table 2.

[0091] Table 2 Data of symmetrical battery long cycle test for Examples 1 to 7 and Comparative Examples 1-2

[0092]

[0093] Experimental Example 3:

[0094] The all-solid-state batteries containing alloy-type negative electrodes and elastic electrolytes obtained in Examples 1 to 11 were subjected to rate and long cycle tests. The voltage window of lithium-ion batteries was 2.5 to 4.5 V, and the voltage window of sodium-ion batteries was 2.7 to 4.2 V. The current density of the rate test was selected as follows: 0.1C, 0.2C, 0.3C, 0.4C, and 0.5C, and the current density of the long cycle test was 0.2C. The battery test was carried out at 60°C. The experimental results are shown in Table 3:

[0095] Table 3 Data of rate and long cycle tests of all-solid-state batteries of Examples 1 to 11 and Comparative Examples 1-2

[0096]

[0097] It can be clearly seen from the results in Table 1 that the electrolyte is significantly superior to the common PEO-based solid electrolyte in ionic conductivity, mechanical properties and flame retardant properties. It is well known that the ionic conductivity and elastic modulus of solid electrolytes restrict each other and increase and decrease at the same time. When the mass fraction of elastic polymer monomer is 40%-70%, it can provide excellent elastic modulus and high ionic conductivity for the electrolyte; when the mass fraction of plasticizer is 30-60%, the force between polymer segments is weakened and the molecular chain movement is enhanced, resulting in a significant improvement in the ionic conductivity of the electrolyte. Based on the intrinsic excellent elastic modulus of the elastomer, the electrolyte still maintains a high elastic modulus. The results in Table 1 show that within the range of the limited orthogonal experimental results, when the weight ratio of elastic polymer to lithium salt is 2:1 and 20% plasticizer is added, the electrolyte has both high ionic conductivity and good elastic modulus, which is significantly better than the non-elastic electrolyte.

[0098] The symmetric cell and full cell data in Tables 2 and 3 fully confirm the above conclusions. For the alloy-type negative electrode, compared with the currently reported solid electrolytes, the solid electrolyte prepared by this method exhibits more excellent mechanical and electrochemical properties.

[0099] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. An all-solid-state battery comprising an alloy-type negative electrode and an elastic electrolyte, characterized in that: It includes an alloy type negative electrode, an elastic electrolyte and a positive electrode; the elastic electrolyte is tightly combined with the alloy type negative electrode and the positive electrode in an in-situ or non-in-situ manner, and the combination method includes any one of the following methods: (1) After the elastic electrolyte is pre-cured, it is coated on one side of the alloy-type negative electrode and continues to cure; (2) After the elastic electrolyte is pre-cured, it is coated on one side of the alloy type negative electrode, and after being attached to the positive electrode, it continues to cure; (3) The precursor solution of the elastic electrolyte is injected between the alloy-type negative electrode and the positive electrode and solidified; The elastic electrolyte comprises an elastic polymer matrix and a metal salt; the elastic polymer matrix comprises one or more of a thermosetting elastomer, a thermoplastic elastomer, or a copolymer or a mixture mainly composed of the above thermosetting / thermoplastic elastomer; the ionic conductivity of the elastic electrolyte is 0.5×10 -4 ~100.0×10 -4 S cm -1 , thickness is 5 to 1000 μm, elastic deformation is 50 to 500%, and has flame retardant properties.

2. The all-solid-state battery according to claim 1, characterized in that: The all-solid-state battery is selected from a primary battery or a secondary battery.

3. The all-solid-state battery according to claim 2, characterized in that: The all-solid-state battery is selected from any one of a lithium battery, a sodium battery, a potassium battery, a magnesium battery, a calcium battery, and an aluminum battery.

4. The all-solid-state battery according to claim 1, characterized in that: The alloy-type negative electrode includes metal / non-metal and its compound that can form an alloy with metal ions, and the metal ions are any one of lithium ions, sodium ions, potassium ions, magnesium ions, calcium ions, and aluminum ions.

5. The all-solid-state battery according to claim 1, characterized in that: Optionally, the elastic electrolyte further comprises a plasticizer.

6. The all-solid-state battery according to claim 1, characterized in that: The elastic polymer matrix includes one or more of thermosetting elastomers and thermoplastic elastomers, or a copolymer or mixture mainly composed of the above thermosetting / thermoplastic elastomers; the thermosetting elastomer is selected from one or more of natural rubber, isoprene rubber, polybutadiene rubber, styrene-butadiene rubber, nitrile rubber, and chloroprene rubber; the thermoplastic elastomer is selected from one or more of hydrogenated ethylene-butylene rubber, polyamide, polyolefin, and polyurethane.

7. The all-solid-state battery according to claim 1, characterized in that: The metal salt includes one or more of an inorganic salt and an organic salt; the inorganic salt is selected from one or more of perchlorate, tetrafluoroborate, hexafluoroarsenate, and hexafluorophosphate; the organic salt is selected from one or more of bis(oxalyl)borate, difluorooxalyl)borate, bis(difluorosulfonyl)imide salt, and bis(trifluoromethyl)sulfonyl)imide salt.

8. The all-solid-state battery according to claim 5, characterized in that: The plasticizer in the electrolyte includes one or more organic molecules of alcohol, phenol, ether, acid, aldehyde, ketone, ester, nitrile, amine and ionic liquid.

Citation Information

Patent Citations

  • Lithium-protecting polymer composite layer for a lithium metal secondary battery and manufacturing method

    US20220190346A1